The Effectiveness of the Door to Door System Bhabinkamtibmas in Preventing Theft with Weights to Realize Kamtibmas at Madiun Police - Rafid, Muhammad (Indonesian Journal of Police Studies, 2024)
This research focuses on the role of Bhabinkamtibmas in preventing criminal acts of theft with weights in the Madiun Regency area, against the background of Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia. Conducted in the Madiun Police jurisdiction, this research explores the implementation of Bhabinkamtibmas through the Door to Door system method. The problem formulation includes its effectiveness in preventing criminal acts of theft with weights as well as factors that influence its performance. In his analysis, the author uses the theory of Effectiveness, Social Control, and SWOT analysis to understand the role of Bhabinkamtibmas in Door to Door system outreach activities and the factors that influence it. The author uses a qualitative field research approach to explore the factors that influence the role of Bhabinkamtibmas in preventing criminal acts of theft with weighting in Madiun. By interviewing and collecting descriptive data from various sources, this research provides an in-depth picture of this problem. The results of the research show that even though there is one Bhabinkamtibmas village, there are still shortcomings in implementing the Door to Door system, especially in planning, organizing and implementation which is not yet optimal. However, the effectiveness of Bhabinkamtibmas in realizing social security through door to door system activities has been proven, but improvements are still needed in the management of these activities so that they are more effective in the future.